Consumer Perception, Promotion, Price, and Product Quality on Customer Satisfaction of Wardah Products in Langsa City - Adriliani, Dea; Meutia, Rahmi (Management Science Doctoral Program, Pasundan University, 2023)
This study aims to determine whether Consumer Perceptions, Promotions, Prices and Product Quality affect Consumer Satisfaction with Wardah Products in Langsa City. This study used a sample of 96 respondents with the criteria of having used wardah products and having ages ranging from 20 years and over. The basic analysis method uses multiple linear regression, t test, F test and coefficient of determination test (Adjusted R2). The results of this study show Y = 3.150 + 0.211X1 + 0.045X2 – 0.161X3 + 0.473X4. The results of the t test stated that the consumer perception factor had a significant effect on consumer satisfaction with wardah products in Langsa City, the promotion factor had no significant effect on consumer satisfaction with wardah products in Langsa City, the price factor had a significant effect on customer satisfaction with wardah products in Langsa City, and product quality factors have a significant effect on consumer satisfaction with wardah products in Langsa City. The results of the F test stated that consumer perceptions, promotions, prices and product quality simultaneously had a significant effect on consumer satisfaction with wardah products in Langsa City. The result of the coefficient of determination (Adjusted R2) is 0.596 or 59.6% while the remaining 40.4% is influenced by other variables not examined in this study.